Ultrasonic pest repeller / Khairul Anwar Abdul Razak and Azhar Shahidan - Abdul Razak, Khairul Anwar; Shahidan, Azhar (2003)
Ultrasonic pest repeller is some sort of repeller that we used in order to repelled the insect and pest. This repeller is not the same as in the current market. We say this because the repeller that we have designed is based on the convenient of the user. We have design the repeller that have small in size which make it is easier to carry anywhere. This repeller is designed to use the wave between the ranges of 30 kHz to 50 kHz. Human being can’t hear these high-frequency sounds. Unfortunately, all pests do not react at the same ultrasonic frequency. While some pests get repelled at 35 kHz, some others get repelled at 38 to 40 kHz. To increase the effectiveness, this circuit is designed to make it able to vary the frequency. The frequency can be varied in certain limits step by step automatically. Here are 5 steps of variation are used but the same can be extended up to 10 steps, if desired. For each clock pulse output from op-amp IC1 CA3130, the logic 1 output of 1C2 CD4017shifts from Q0 to Q4 (or QO to Q9). 5 presets VR2 through VR6 are set at the different values. VR1 is used to change the clock pulse rate. 1C3 is wired as an astable multivibrator operating at a frequency nearly 80 kHz. Its output is not symmetrical. 1C4 is CD4013, a D-type flip-flop which delivers symmetrical 40kHz signals at its Q and Q outputs which are amplified in push-pull made by transistor Tl, T2, T3 and T4 to drive a lower cost, high frequency piezo tweeter. For frequency adjustments, you may use the oscilloscope. It can be done by trial and error also if you do not have the oscilloscope. This pest repeller to be much more effective then those published earlier because here ultrasonic frequency is automatically changed to cover the different pests and the output power is also sufficiently high.